2023
DOI: 10.1021/acs.energyfuels.2c03299
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional SnO2-ZnO Nanohybrid Electrode Fabricated via Atomic Layer Deposition for Electrochemical Supercapacitors

Abstract: Two-dimensional (2D) heterostructures of transition metal oxides (TMOs) are promising candidates for high-performance electrochemical supercapacitors (ESCs). Herein, sub-10 nm 2D SnO2-ZnO heterostructures were constructed on Au-modified SiO2/Si wafers by an atomic layer deposition (ALD) technique for ESC application. The cyclic voltammetry (CV) study revealed the pseudocapacitive-type Faradaic redox reactions of the 2D SnO2-ZnO heterostructure electrode with good reversibility. The electrode exhibited high ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Within this range of ALD, most of the deposited metal oxide films are amorphous. Our previous studies on ultra-thin TiO 2 [11], WO 3 [15], Ga 2 O 3 [16], In 2 O 3 [7], MoO 3 [12] and SnO 2 [17] films deposited on an Au substrate at the ALD window of 100 • C to 250 • C under O 2 plasma confirmed the semi-amorphous nature of these films.…”
Section: Introductionmentioning
confidence: 58%
“…Within this range of ALD, most of the deposited metal oxide films are amorphous. Our previous studies on ultra-thin TiO 2 [11], WO 3 [15], Ga 2 O 3 [16], In 2 O 3 [7], MoO 3 [12] and SnO 2 [17] films deposited on an Au substrate at the ALD window of 100 • C to 250 • C under O 2 plasma confirmed the semi-amorphous nature of these films.…”
Section: Introductionmentioning
confidence: 58%
“…Metal oxides have significant potential for development in the field of photocatalysis, sewage treatment, and electrochemical hydrogen storage due to their stable structure, low development cost, and excellent electrochemical performance. , TiO 2 , Fe 2 O 3 , ZnO, SiO 2 , and Co 3 O 4 are commonly used metal oxides. Lopa et al prepared 2D SnO 2 –ZnO heterostructures by atomic layer deposition technique. It was found that the 2D electrodes exhibited excellent electrochemical performance with capacity retention up to 96.3% after 5000 cycles.…”
Section: Electrochemical Hydrogen Storage Materialsmentioning
confidence: 99%
“…[34][35][36][37][38][39] Carbons, metal oxides, selenides, nitrides, carbides, sulfides, and phosphides are some of the many materials investigated for their potential in electrochemical energy storage devices. [40][41][42][43][44][45][46][47] The properties of metal chalcogenides (MCs) make them ideal candidates for in-depth research as electrode material for SCs. [48][49][50] The weaker MÀ C (where C represents S, Te, and Se) bonds, as compared to MÀ O bonds, [51][52][53][54] result in MCs exhibiting higher capacity, electronic conductivity, and more facile ion transport pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Carbons, metal oxides, selenides, nitrides, carbides, sulfides, and phosphides are some of the many materials investigated for their potential in electrochemical energy storage devices [40–47] . The properties of metal chalcogenides (MCs) make them ideal candidates for in‐depth research as electrode material for SCs [48–50] .…”
Section: Introductionmentioning
confidence: 99%